Community Sensor Network for Monitoring Road Roughness Using Smartphones - Kumar, R.; Mukherjee, Abhijit; Singh, V. (American Society of Civil Engineering, 2017)
© 2016 American Society of Civil Engineers.Maintenance of ever-expanding road networks all over the world is a critical task and regular monitoring of the road surface is imperative for successful maintenance. Existing monitoring techniques use dedicated vehicles equipped with sensors. Limited availability of these specialized vehicles makes regular monitoring very challenging. This paper explores a novel approach of empowering the smartphone user community for monitoring roads that they use. Smartphones are used for sensing the road surface conditions from a moving vehicle. The system involves client applications on smartphones that collect accelerations as the users travel on the roads, processing of the information and communication to a central server, georeference database, and visualization of road conditions on Google maps. In this paper, the fuzzy logic-based road surface roughness classification is proposed for monitoring the road roughness. The implementation has been demonstrated in different road networks at northern region of India. The experiment demonstrates the huge potential of user community participation in maintenance of road infrastructure.